Does hand stiffness reflect internal organ fibrosis in diabetes mellitus? - Phatak, Sanat; Ingram, Jennifer L.; Goel, Pranay; Rath, Satyajit; Yajnik, Chittaranjan (Frontiers in Clinical Diabetes and Healthcare, 2023)
Fibrosis leads to irreversible stiffening of tissue and loss of function, and is a common pathway leading to morbidity and mortality in chronic disease. Diabetes mellitus (both type 1 and type 2 diabetes) are associated with significant fibrosis in internal organs, chiefly the kidney and heart, but also lung, liver and adipose tissue. Diabetes is also associated with the diabetic cheirarthropathies, a collection of clinical manifestations affecting the hand that include limited joint mobility (LJM), flexor tenosynovitis, Duypuytren disease and carpal tunnel syndrome. Histo-morphologically these are profibrotic conditions affecting various soft tissue components in the hand. We hypothesize that these hand manifestations reflect a systemic profibrotic state, and are potential clinical biomarkers of current or future internal organ fibrosis. Epidemiologically, there is evidence that fibrosis in one organ associates with fibrosis with another; the putative exposures that lead to fibrosis in diabetes (advanced glycation end product deposition, microvascular disease and hypoxia, persistent innate inflammation) are ‘systemic’; a common genetic susceptibility to fibrosis has also been hinted at. These data suggest that a subset of the diabetic population is susceptible to multi-organ fibrosis. The hand is an attractive biomarker to clinically detect this susceptibility, owing to its accessibility to physical examination and exposure to repeated mechanical stresses. Testing the hypothesis has a few pre-requisites: being able to measure hand fibrosis in the hand, using clinical scores or imaging based scores, which will facilitate looking for associations with internal organ fibrosis using validated methodologies for each. Longitudinal studies would be essential in delineating fibrosis trajectories in those with hand manifestations. Since therapies reversing fibrosis are few, the onus lies on identification of a susceptible subset for preventative measures. If systematically validated, clinical hand examination could provide a low-cost, universally accessible and easily reproducible screening step in selecting patients for clinical trials for fibrosis in diabetes.